2005
DOI: 10.1136/bjo.2004.048686
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal expansion as a mechanism for acute primary angle closure: an investigation into the change of biometric parameters in the first 2 weeks

Abstract: Background/aim: Choroidal expansion with anterior movement of the lens was recently proposed as a mechanism for acute primary angle closure (APAC). The aim of this study was to compare the biometric parameters, central anterior chamber depth, limbal chamber depth, lens thickness, and lens position, within 24 hours of presentation and 2 weeks later in eyes with APAC. Methods: This was a prospective observational case series of 41 subjects with APAC. Subjects who presented with APAC were treated with medical the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…Subsequently, the degree of glaucoma damage was not consistently associated with choroidal thickness 22. The results of our study agree with the findings by Yang et al 23 who did not find any change in the lens position, relative lens position or axial length in both affected and fellow eyes of patients within 24 h of presentation and 2 weeks later after the APAC. The authors concluded that their findings did not support the hypothesis of a lens movement due to choroidal expansion in APAC.…”
Section: Discussionsupporting
confidence: 90%
“…Subsequently, the degree of glaucoma damage was not consistently associated with choroidal thickness 22. The results of our study agree with the findings by Yang et al 23 who did not find any change in the lens position, relative lens position or axial length in both affected and fellow eyes of patients within 24 h of presentation and 2 weeks later after the APAC. The authors concluded that their findings did not support the hypothesis of a lens movement due to choroidal expansion in APAC.…”
Section: Discussionsupporting
confidence: 90%
“…It is conceivable that a multilevel physiological trigger may initiate a sustained choroidal expansion, which in an anatomically predisposed eye, leads to APAC and PACG. Conversely, the fact that other investigators have failed to demonstrate significant changes in biometry (ACD, lens position, RLP) before and 2 weeks after LPI [39], challenges the theory of anterior lens movement secondary to choroidal expansion as a possible mechanism for APAC. It would be interesting to perform serial UBM among those with newly diagnosed PACG post LPI to establish a temporal sequence of events.…”
Section: Choroidal Expansion/effusionmentioning
confidence: 90%
“…These changes were consistent with previous reports analysing quantitatively. [8][9][10][11][12][13][14][15][16] We did not measure the angle opening distance (AOD), because the software in AS-OCT only includes a measuring system capable of calculating distance and angle.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have assessed the change of anterior segment morphology using the abovementioned techniques, and most of them believed that the peripheral anterior chamber was deepened and the anterior angle was widened significantly after LPI, whereas the central anterior chamber was not changed. [8][9][10][11][12][13][14][15][16] However, all of the above methods might have some limitations. Either the accommodation or the illumination could not be controlled, or the examination would touch the eyes, thereby causing some measuring errors.…”
Section: Introductionmentioning
confidence: 99%